IMPLEMENTATION OF A WEB-BASED TALENT ACQUISITION ADMINISTRATION INFORMATION SYSTEM AT PT GUNA GLOBAL PERSADA - Zulfa Laila Nabilla; Nining Suharyanti (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2026)
PT Guna Global Persada is a company engaged in human resource management services (outsourcing). The current talent acquisition administration process is still carried out manually, with separate record-keeping using spreadsheets and non-integrated communication channels. This situation creates various problems such as difficulty tracking candidate data, data duplication, delays in updating workforce requirements, and low efficiency of the Talent Acquisition team. This research aims to implement an integrated web-based talent acquisition administration information system to improve the effectiveness, efficiency, and accuracy of data management. The system development method used is the Waterfall method, consisting of communication, planning, modeling, construction, and deployment stages. The system was designed using Unified Modeling Language (UML) modeling in the form of use case diagrams, activity diagrams, sequence diagrams, and class diagrams. The database design was carried out using Entity Relationship Diagrams (ERDs) and Logical Record Structures (LRSs). The results of the study indicate that the implemented web-based information system is capable of managing candidate data, client data, workforce requirements, selection processes, placement, and reporting in an integrated manner. This system has been proven to reduce data duplication, accelerate administrative processes, improve data accuracy, and support management decision- making. Thus, the developed system is able to improve the operational performance of the Talent Acquisition team and support the company's business processes more effectively and efficiently.